Eschatologie v díle Jana Husa. - Mazalová, Lucie (Spisy Masarykovy univerzity v Brně, Filozofická fakulta ;, 2015)
The paper deals with the question of what the significance of the last matters and eschatology was for Hus and what role they played within his work. The author solves this topic from the perspective of Latin medievistics, namely on the basis of the analysis of the content, linguistics, and literary and historical background. The work studies in detail selected Husś sermons (Confirmate corda vestra, Diliges Dominum Deum, State succincti, Dixit Martha and Spiritum nolite extinguere) and Husś correspondence; nevertheless, it also takes into consideration his other relevant works. Moreover, wor.